Cognitive psychology connecting mind, research, and everyday experience - Goldstein, E. Bruce 1941- (Cengage Learning, 2019)
"Connecting the study of cognition to everyday life, E. Bruce Goldstein's COGNITIVE PSYCHOLOGY: CONNECTING MIND, RESEARCH, AND EVERYDAY EXPERIENCE, 5th Edition, gives equal treatment to both the landmark studies and the cutting-edge research that define this fascinating field. Concrete examples and illustrations help students understand the theories of cognition--driving home both the scientific importance of the theories and their relevance to students' daily lives. Goldstein's accessible narrative style blends with an art program that makes difficult concepts understandable. Students gain a true understanding of the "behind the scenes" activity that happens in the mind when humans do such seemingly simple activities as perceive, remember or think. Goldstein also focuses on the behavioral and physiological approaches to cognition by including physiological materials in every chapter."--R?esum?e de l'?editeur.